Determinants of business performance in Metropolitan Lima during the COVID-19 pandemic - Ramos Reyes, Joshep Ivan (2021)
Objective: Identify the determining factors that explain the poor business performance in Metropolitan Lima during the COVID-19 pandemic. Method: Factor analysis was used to group the problems that Metropolitan Lima companies faced during the COVID-19 pandemic, and to identify the main factors associated with these problems. Subsequently, the effects that the factors had on business performance were estimated, which are understood as the companies' sales index. Results: The factors associated with liquidity and operational problems had a negative and statistically significant effect on the companies' sales index. However, the factor associated with liquidity problems was decisive in explaining the behavior of the sales index in companies in Metropolitan Lima during the COVID-19 pandemic. Conclusion: The problems associated with access to financing and lack of liquidity of companies are the ones that explain to a greater extent the poor business performance in Metropolitan Lima during the COVID-19 pandemic.